Body impedance analysis to estimate malnutrition in inflammatory bowel disease patients – A cross‐sectional study. Issue 12 (9th March 2023) - Reiner, Johannes; Koch, Kristina; Woitalla, Julia; Huth, Astrid; Bannert, Karen; Sautter, Lea; Jaster, Robert; Witte, Maria; Lamprecht, Georg; Schäffler, Holger
Abstract : Objective: Malnutrition is a common clinical problem in patients with inflammatory bowel diseases (IBD). However, a gold standard for the detection of malnutrition in IBD patients is lacking. Methods: A cross‐sectional study to assess malnutrition in patients with IBD and healthy controls (HCs). Clinical characteristics (Montreal classification, disease activity, previous surgery) and mutations in the NOD2 gene in patients with Crohn's disease (CD) were obtained. We performed a nutritional assessment with screening for nutritional risk and diagnosis for malnutrition (Malnutrition Universal Screening Tool [MUST]) score, NRS‐2002, European Society for Clinical Nutrition and Metabolism (ESPEN), and Global Leadership Initiative on Malnutrition (GLIM) criteria and performed body impedance analysis (BIA). Results: 101 IBD patients (57 CD and 44 ulcerative colitis (UC) and 50 HC were included in a single northern German tertiary center. GLIM criteria detected malnutrition significantly more often compared to the ESPEN criteria. Active disease, a long‐standing disease course, and previous surgery were associated with reduced muscle mass. IBD patients had a higher fat mass index compared to HC. Mutations in the NOD2 gene had no effect on nutritional status. Conclusions: The GLIM criteria detect malnutrition at a higher rate compared to ESPEN. Specific disease factors might put IBD patients at a higher risk for the development of malnutrition, so these patients might benefit from a frequently performed screening, which might result in a favorable disease course. Abstract : Although malnutrition is a common phenomenon in inflammatory bowel disease (IBD), a gold standard for its diagnosis is still lacking. We performed a cross–sectional study in IBD patients and healthy controls and compared different screening and assessment methods for malnutrition. As a result, the Global Leadership Initiative on Malnutrition (GLIM) score detected malnutrition more often compared to the European Society for Clinical Nutrition and Metabolism (ESPEN) criteria. Abbreviations: BMI, body mass index; MUST, Malnutrition Universal Screening Tool; NRS, nutritional risk screening